Development and application of a scoring system to rate malnutrition screening tools used in older adults in community and healthcare settings – A MaNuEL study. Issue 4 (August 2019) - Power, Lauren; de van der Schueren, Marian A.E.; Leij-Halfwerk, Susanne; Bauer, Jürgen; Clarke, Michelle; Visser, Marjolein; Volkert, Dorothee; Bardon, Laura; Gibney, Eileen; Corish, Clare A.; ,
Summary: Rationale: Many malnutrition screening tools are used to screen for risk of malnutrition in older adults. An aim of the Joint Programming Initiative (JPI) 'A Healthy Diet for a Healthy Life' (HDHL) MalNutrition in the ELderly Knowledge hub (MaNuEL) is to devise recommendations on the best tools to screen for risk of malnutrition in older adults in community and healthcare settings across Europe. The aim of this paper was to develop and apply a scoring system to rate malnutrition screening tools. Methods: Using a targeted literature search strategy, 48 malnutrition screening tools used to screen for risk of malnutrition in older adults were identified across community, rehabilitation, residential care and hospital settings. Criteria to rate each tool were developed; these were based on published evidence and expert opinion. These criteria were translated into a scoring system. Results: The scoring system had three equally weighted sections; validation, parameters and practicability, and was applied to all 48 tools. Overall, the highest scoring tools per setting for screening for risk of malnutrition in older adults were i) DETERMINE your health checklist for the community setting; ii) the Nutritional Form for the Elderly (NUFFE) for the rehabilitation setting; iii) the Short Nutritional Assessment Questionnaire-Residential Care (SNAQ RC ) for residential care and iv) both the Malnutrition Screening Tool (MST) and the Mini Nutritional Assessment Short Form Version 1 (MNA-SF-V1) for the hospital setting. Conclusion: Setting-specific tools are more appropriate for use with older adults. These findings will inform recommendations for the optimal screening of geriatric malnutrition across Europe.